ABROGATION OF ARTICLE 370 AND ITS CONSTITUTIONAL IMPLICATIONS - Gupta, Divya; Mankotia, Anu (Journal of Ecohumanism, 2025)
At the time of Indian independence, the State of Jammu and Kashmir was not a province of the erstwhile British India, and, therefore, was given an option, after independence, either or not to join any of the two newly created countries of India and Pakistan. When the ruler of the State, Maharaja Hari Singh, decided to join India by executing ‘Instrument of Accession’ (I A) on October 26, 1947; the State was accorded special status under Article 370 of Indian Constitution. Under the provisions of this Article, limitations were imposed on legislative and executive powers of the Government of India as per the terms of the I A. Presidential order, supported by the Government of the State, was a condition precedent under Article 370 to implement any of the provisions of Indian Constitution in the State. Enjoying the special status, the State had framed its own Constitution in 1956 for its people. Government of India has abrogated, on August 5, 2019, the special status of the State by utilizing the provisions of Article 370 itself, and has, in addition, bifurcated it into two Union Territories of ‘Jammu and Kashmir’ and ‘Ladakh’. The Constitutionality of this legal action, however, is pending before our Supreme Court and a future verdict in the case will decide the status of the former State of Jammu and Kashmir.